Subacute behavior of glucose and blood pressure of type 1 diabetic people after strength exercise session: Study protocol - Fernandes Camilo, Victor; Almeida Pires Franco de Oliveira, Bruna; Ribeiro da Costa, Matheus André; Urzêda Vitória, Estela; Mendes de Faria Sudré, Tamyris; Oliveira, Rodrigo Franco de (Manual Therapy, Posturology & Rehabilitation Journal, 2024)
Background: Type 1 Diabetes Mellitus (DM1) is characterized as a severe insulin deficiency resulting from the destruction of beta cells in the pancreas, associated with autoimmunity. The clinical picture of a patient with DM1 includes symptoms such as abnormal thirst, dry mouth, sudden weight loss, frequent urination, lack of energy, tiredness, constant hunger and blurred vision. Systemic arterial hypertension (SAH) is characterized by high levels of pressure in the arteries, being associated with risk factors for coronary artery disease; cerebrovascular accident (CVA); myocardial infarction; heart failure and kidney failure. Regular physical activity in these patients is associated with a reduced risk of future cardiovascular disease, better long-term glycemic control, better cardiovascular fitness, better quality of life, reduced daily insulin requirements and better weight control. Furthermore, it plays an important role in the primary and secondary prevention of diabetes cardiovascular disease, improving general health and well-being. Objective: The present study aims to evaluate the effects of strength training on glycemic parameters after an exercise session, in adult type 1 diabetic individuals, through a randomized controlled clinical trial. Methodology: The sample will be made up of 30 participants with DM1, made up of men and women based on the inclusion/exclusion criteria. Discussion: Practicing physical activity reduces the need for hypoglycemic drugs, also improves metabolic control and helps obese patients lose weight, reducing the risk of cardiovascular diseases and improving the quality of life of these patients. The practice of strength and aerobic training as a non-drug treatment is systematically found in the literature as a fundamental strategy for reducing systemic arterial hypertension and maintaining the cardiovascular system. Both resistance exercise and Pilates are effective for individuals with type 1 diabetes, improving metabolic and clinical control, especially when combined with adequate nutrition and amino acid supplementation. Physical activities reduce the need for hypoglycemic medications, help with weight loss and reduce the risk of cardiovascular diseases. Regular exercise, especially intermittent, significantly reduces the risk of acute hypoglycemia. Furthermore, it improves HDL and LDL levels, essential for reducing cardiovascular risks. Strength and aerobic training are essential for controlling high blood pressure and improving quality of life, with three weekly sessions being recommended for satisfactory results.